Firms' Off‐Balance Sheet and Hybrid Debt Financing: Evidence from Their Book‐Tax Reporting Differences - MILLS, LILLIAN F.; NEWBERRY, KAYE J. (Journal of Accounting Research, 2005)
ABSTRACT We match large U.S. corporations' tax returns during 1989–2001 to their financial statements to construct a firm‐level proxy of firms' use of off‐balance sheet and hybrid debt financing. We find that firms with less favorable prior‐period Standard & Poor's (S&P) bond ratings or higher leverage ratios in comparison to their industry report greater amounts of interest expense on their tax returns than to investors and creditors on their financial statements. These between‐firm results are consistent with credit‐constrained firms using more structured financing arrangements. Our within‐firm tests also suggest that firms use more structured financing arrangements when they enter into contractual loan agreements that provide incentives to manage debt ratings. Specifically, we find that after controlling for S&P bond rating and industry‐adjusted leverage, our sample firms report greater amounts of interest expenses for tax than for financial statement purposes when they enter into performance pricing contracts that use senior debt rating covenants to set interest rates. Furthermore, we find that the greatest book‐tax reporting changes occur when firms become closer to violating these debt rating covenants. These latter findings are consistent with firms' contractual debt covenants influencing their use of off‐balance sheet and hybrid debt financing.